A quinazoline-based HDAC inhibitor affects gene expression pathways involved in cholesterol biosynthesis and mevalonate in prostate cancer cells. Issue 3 (13th January 2016) - Lin, Z.; Bishop, K. S.; Sutherland, H.; Marlow, G.; Murray, P.; Denny, W. A.; Ferguson, L. R.
Abstract : Chronic inflammation can lead to the development of cancers and resolution of inflammation is an ongoing challenge. Abstract : Chronic inflammation can lead to the development of cancers and resolution of inflammation is an ongoing challenge. Inflammation can result from dysregulation of the epigenome and a number of compounds that modify the epigenome are in clinical use. In this study the anti-inflammatory and anti-cancer effects of a quinazoline epigenetic-modulator compound were determined in prostate cancer cell lines using a non-hypothesis driven transcriptomics strategy utilising the Affymetrix PrimeView® Human Gene Expression microarray. GATHER and IPA software were used to analyse the data and to provide information on significantly modified biological processes, pathways and networks. A number of genes were differentially expressed in both PC3 and DU145 prostate cancer cell lines. The top canonical pathways that frequently arose across both cell lines at a number of time points included cholesterol biosynthesis and metabolism, and the mevalonate pathway. Targeting of sterol and mevalonate pathways may be a powerful anticancer approach.